New Forms of the Organization of the Educational Process at HSE: Students’ and Teachers’ Evaluations - Radaev, Vadim; Fursov, Konstantin; Mel’nikovVadim (Voprosy obrazovaniya / Educational Studies Moscow, 2010)
The article presents the results of representative polls of students and teachers of all faculties at HSE. The polls were conducted by the student interest goup Gorod (City) as part of the annual monitoring of university life. The polls investigated the attitude of the respondents to new features of university life, such as the module system, the week of selfpreparation between modules, the emphasis on written forms of grading, the 10-point system of grades, the credit system, student and teacher ratings. The research showed that the attitude of students and teachers to these innovations is in general positive. However, some points remain controversial.